ỨNG DỤNG PHƯƠNG PHÁP SẮC KÝ LỎNG KHỐI PHỔ ĐỂ NHẬN DIỆN CÁC SẢN PHẨM TRUNG GIAN CỦA CÁC PHẢN ỨNG QUANG PHÂN 2,4,6-TRINITRORESOXIN (TNR) - Khuê, Đỗ Ngọc; Chất, Nguyễn Văn; Lân, Phạm Hồng (Vietnam Journal of Chemistry, 2012)
The study of the mechanism of photochemistry and photocatalytic TNR by application of HPLC-MS combine with methods to examine TOC and quantify TNR with and without oxidants and determining intermediary agents of photochemistry and photocatalytic simultaneously is also discussed.